2002
DOI: 10.1002/1521-3803(20020501)46:3<204::aid-food204>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Content of strontium, lithium and calcium in selected milk products and in some marine smoked fish

Abstract: The strontium, lithium and calcium contents have been determined in 87 samples of five kinds of milk-fermented products, as well as in 93 samples of ten kinds of marine smoked fish. The samples were purchased on the local market. The representative samples were dry ashed in quartz crucibles and the ash was treated with suitable amounts of conc. HCl and a few drops of conc. HNO3. The obtained sample solution was then used for the determination of Sr, Li and Ca by the flame atomic absorption spectrometry (AAS) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 8 publications
2
21
1
Order By: Relevance
“…The lowest Sr levels were found in paella and tarama (less than 0.70 mg/kg). These results were similar (Nabrzyski & Gajewska, 2002;Tetsuro et al, 2007), lower (Shiraishi, 2005;Tetsuro et al, 2005) or higher (Kelly et al, 2008;Mohapatra et al, 2009) than mean values previously found in fish and other seafood.…”
Section: Strontiumsupporting
confidence: 85%
See 1 more Smart Citation
“…The lowest Sr levels were found in paella and tarama (less than 0.70 mg/kg). These results were similar (Nabrzyski & Gajewska, 2002;Tetsuro et al, 2007), lower (Shiraishi, 2005;Tetsuro et al, 2005) or higher (Kelly et al, 2008;Mohapatra et al, 2009) than mean values previously found in fish and other seafood.…”
Section: Strontiumsupporting
confidence: 85%
“…These mean levels were similar for fish and slightly lower for other seafood compared to those found during the 1st TDS in fish (n = 62; mean 0.030 mg/kg; max 0.106 mg/kg in canned sardines) and in other seafood (n = 18; mean 0.123 mg/kg; max 0.485 mg/kg in mussel) (Leblanc et al, 2005). These results were lower than mean values previously found in fish and other seafood (Nabrzyski & Gajewska, 2002;Shiraishi, 2005).…”
Section: Lithiumcontrasting
confidence: 52%
“…Aside from therapy, Li can be naturally obtained from the diet with main food sources including cereals, potatoes, tomatoes, cabbage, dairy products (i.e., milk and yogurt), and in some mineral- and tap-water (depending on geographical location) ( 9 12 ). In a recent study by Bridge et al ( 13 ), Greek yogurt (GY) supplementation enhanced fat free mass (FFM) gains, biceps thickness, and total strength after a 12-week resistance and plyometric exercise program in untrained, university-aged males ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was more accurate to get NOAEL using food that contained strontium sulfate but did not add calcium. In addition, except for drinking water, Sr from food also made a significant contribution, especially in seafood which contained up to 25 mg/kg of Sr (Nabrzyski and Gajewska 2002). Besides, cooking with drinking water containing a high Sr concentration would increase the intake of Sr as well (Melnyk et al 2019).…”
Section: Limitationsmentioning
confidence: 99%